PERFORMANCE ANXIETY AND SLEEP PROBLEMS AS PREDICTORS OF ACADEMIC ACHIEVEMENT - Shahzadi, Namra; Arshad, Misbah (International Journal of Research -GRANTHAALAYAH, 2017)
The present study investigated performance anxiety and sleep problems as predictors of academic achievement among a convenience sample of 100 university students (Male = 43, Female = 57). Method: The participants, aged 18 to 25 years, were selected from three different departments of University of Gujrat. Hamilton Anxiety Scale (Hamilton, 1959) and Pre Sleep Arousal Scale (Nicassio, Mendlowitz, Fussell, & Petras, 1989) were individually administered to the participants in their respective departments. Academic achievement was measured in terms of GPA of previous semester of each respondent. Results: The Cronbach Alphas for both the scales for the present sample fell in acceptable range (α = 0 .84 - 0.87). Linear regression analyses indicated that performance anxiety significantly predicted (p <.01, p<.001) of low academic achievement among university students. It was also identified that the higher level of performance anxiety was also a strong predictor (p < .0.001) of sleep problems among students. Conclusions: Discussion includes implications for future research and practices with reference to Pakistani culture.